A comprehensive review of Uniform Solar Illumination at Low Concentration Photovoltaic (LCPV) Systems - Amanlou, Yasaman; Hashjin, Teymour Tavakoli; Ghobadian, B.; G., Najafi; R., Mamat (Elsevier, 2016)
Conventional high performance silicon solar cells have a potential to generate more electricity by using low concentrating reflectors. Static solar concentrators reduce the cost of photovoltaic systems for given electrical power demand. However, non-uniform illumination on the conventional rectangular photovoltaic panel causes ohmic drops, mainly due to the cell that operates locally at higher irradiance. In this research study a comprehensive review has been carried out regarding Uniform Solar Illumination at Low Concentration Photovoltaic (LCPV) Systems. Another objective of the present study is therefore, calculating the pattern of sun incident at low concentration ratios for reflective troughs (V-type, cylindrical and compound parabolic concentrators) and linear Fresnel reflectors. The geometrical parameters of these concentrators were studied to obtain uniform illumination on the common rectangular photovoltaic panels. The designed concentrator with most uniform flux distribution, high concentration ratio and low requirement of mirror was fabricated and tested at ambient conditions. The optical simulation output of different concentrators illustrated the linear Fresnel reflector had uniform irradiance on the photovoltaic panel with standard deviation less than 30% of total income radiation. The experimental results showed that the linear Fresnel reflector has the potential to harvest more energy when using standard silicon solar cells in a basic concentration configuration. Finally thermal, electrical and total performances of a photovoltaic/thermal flat collector were measured with and without concentrator. Using the concentrator improved thermal and overall efficiency by 16% and 17.5% respectively. The maximum overall efficiency for PVT collector with concentrator and without concentrator was 91% and 78% respectively.